Evaluating the Remineralizing Potential of Dentifrices Containing Lemon Essential Oil - Varun Chopra; Richa Pathak; P V Samir; Khyati Gupta; DR Mahesh; Vinay Rao (Journal of Pharmacy and Bioallied Sciences)
Aim: The study’s aim to evaluate the remineralization potential of essential oil containing dentifrices. Materials and Methods: Thirty extracted premolars were collected and sectioned at cemento-enamel junction (CEJ) and through buccal and lingual halves. Thirty samples without cracks were embedded into acrylic blocks and examined for baseline hardness level by Vickers hardness tester (VHT). Further, prepared specimens were placed over demineralization solution uninterruptedly for 72 hours and assessment of post-demineralization hardness was done and randomly divided into 3 groups of 15 each: Group 1-Control group: Where no treatment done, Group 2-Calcium and Phosphate group (ENAFIX Anti Cavity Oral Care Toothpaste, Group Pharmaceuticals Ltd., Karnataka, India), Group 3-Lemon essential oil (LEO) group (Perfora Awake Fresh Breath Toothpaste, HCP Wellness Pvt., Gujarat, INDIA.) Remineralizing process was carried out for 14 days utilizing dentifrice slurries and accessing the post-remineralization hardness values. Data were collected and analyzed using analysis of variance (ANOVA). Results: No significant result was found between group 2 and 3. Conclusions: Both dentifrices demonstrated superior remineralization capability. Thus, as a remineralizing agent, LEO containing herbal dentifrices looks to be equally effective as regular toothpaste.